Acute Lymphoblastic Leukemia with a novel dic (11;11) (q24;q24) : A case report - Ismail, Noor Hashim (Iraqi Journal of Cancer and Medical Genetics, 2012)
Cytogenetic study was performed on a case of acute lymphoblastic leukemia . The chromosomal analysis for bone marrow cells by using G- banding technique showed A novel dic (11;11)(q24;q24) in 5 metaphases (15%) of 32 total metaphases studied , which has not been described previously in this leukemia type . Different abnormalities involving chromosome 11q have been reported as well . Novel rearrangement of 11q may reflect the heterogeneity of the genetic change which possibly refers to the differences in environmental and genetic factors of the Iraqi patients in comparison with other patients in another countries, which may contributes in the pathogenesis of acute lymphoblastic leukemia